Analisis Framing Pemberitaan Online Gerakan Indonesia Tanpa Feminis - A’yun Masfupah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2019)
Some time ago an Instagram account called Indonesia without feminists appeared, this account was created as a medium to spread the news that there was a group of people who wanted to eliminate feminism in Indonesia. They say that Indonesia does not need a feminist movement to defend women's rights because even in Islam women have been glorified. Although the Indonesian movement without feminists reaps a lot of responses from both positive and negative people researchers only found a few online news sites that discussed the news, this news was first raised by The Jakarta Post on April 1, 2019 with the headline "My Body Is Not Mine: Indonesia Without Feminists group starts online campaign (My body is not mine: Indonesian group without feminists starts an online campaign) ". Therefore researchers are interested in seeing how the media framing this news. The approach model used is Robert N. Entman's framing analysis model. This model is used to find out about a reality that occurs in the field and how we interpret that reality into content. The media under study is Tribunnews, VOA Indonesia and Political Matter because the three media that were the earliest published news about Indonesia without Feminists after The Jakarta Post. The results of his research can be concluded that the three media have different framing. The Tribunnews news framing emphasizes how responses from various parties and from diverse groups. The focus is more on the response of young people in their 20s such as influencers of social media. While VOA Indonesia, the framing is still the same as Tribunnews, which presents responses from various speakers, which distinguishes the resource person from a particular expert in the field, such as Dr. Nur Rofiah is an interpreter lecturer at the Al-Qur'an College of Sciences. Then the last one is Indonesian Politics, which according to researchers framing their media see from the point of view of those who are pro with the Indonesian movement without feminists, seen from the sources who do not agree with feminism.